In vitro Anti-viral Activity of Psoraleae Semen Water Extract against Influenza A Viruses - Choi, Jang-gi; Jin, Young-Hee; Kim, Ji-Hye; Oh, Tae Woo; Yim, Nam-Hui; Cho, Won-Kyung; Ma, Jin Yeul (Frontiers in Pharmacology, 2016)
Influenza causes respiratory infections and poses health risks to humans and animals; its effects are complicated by increasing resistance to existing anti-influenza viral agents. Therefore, novel therapeutic approaches against influenza virus infection are required. Psoraleae semen has been widely used in traditional medicine in Korea, Taiwan, China, and Japan for treating and preventing various diseases. In this study, we examined the anti-viral activities and mechanism of action of the water extract of Psoraleae semen (WPS) using RAW 264.7 and MDCK cells. We found that pre- and post-treatment with 100 μg/mL WPS markedly inhibited influenza A virus replication as assessed using a green fluorescent protein reporter virus, reduced viral protein expression (NS-1, PA, HA, PB-1, M1, and M2), and inhibited NA and HA activities. Mechanism studies revealed that WPS induced type I interferon cytokine secretion and subsequent stimulation of an anti-viral state in RAW 264.7 cells. Further, WPS exerted inhibitory effects on neuraminidase in influenza virus strains H1N1 and H3N2. Meanwhile, WPS exhibited inhibitory effects on hemagglutination in H3N2 but not in H1N1. Based on these results, WPS serves as an immunomodulator and inhibitor of influenza hemagglutinin and neuraminidase. Our results suggest that WPS is a promising source of novel anti-influenza drug candidates.